Folate intake, serum folate, and risk of esophageal cancer: a systematic review and dose–response meta-analysis. Issue 3 (May 2019) - Ni, Yingchun; Du, Jinge; Yin, Xiaolin; Lu, Ming
Abstract : The dose–response relationship between folate and the risk of esophageal cancer (EC) is not clear. To further elucidate their relationships, we carried out a dose–response meta-analysis of folate intake, serum folate, and the risk of EC. PubMed, Embase, Web of Science, and China National Knowledge Infrastructure were searched for observational studies until September 2016. Then, we carried out a systematic review and dose–response meta-analysis using Stata 14.0 software. Subgroup analyses were further carried out according to study characteristics and adjustment confounders. A total of 23 studies with a total of 3886 patients were enrolled in this study. The pooled odds ratios for EC in the highest versus the lowest levels of folate intake and serum folate were 0.64 (0.54–0.76, P <0.001) and 0.45 (0.19–1.07, P =0.071), respectively. Dose–response meta-analyses were carried out to assess associations between folate intake, serum folate, and EC risk. When serum folate is 10 μg/l higher than the lowest reference dosage (3.44 μg/l), EC decreased risk with an increase in serum folate levels. When folate intake is 50 μg/day higher than the lowest reference dosage (125.21 μg/day), the EC risk is decreased with an increase in folate intake. Finally, the results support that folate can promote public health through decreasing EC risk in a certain dosage range; otherwise, the protective effects might be reduced. Abstract : Supplemental Digital Content is available in the text.